Efficacies of the original and modified World Health Organization-recommended hand-rub formulations. Issue 2 (October 2020) - Suchomel, M.; Steinmann, J.; Kampf, G.
Summary: The World Health Organization (WHO) hand-rub formulations have been in use around the world for at least the past 10 years. The advent of coronavirus disease 2019 (COVID-19) has further enhanced their use. We reviewed published efficacy data for the original and modified formulations. Only efficacy data according to the European Norms (EN) were found. The bactericidal efficacy of the original formulations was, under practical conditions, partly insufficient (EN 1500, only effective in 60 s; EN 12791, efficacy too low in 5 min). The first modification with higher alcohol concentrations improves their efficacy as hygienic hand rub (effective in 30 s). The second (0.725% glycerol) and third (0.5% glycerol) modification improves their efficacy for surgical hand preparation (effective in 5 and 3 min). The original and second modified formulations were tested and demonstrate activity against enveloped viruses including severe acute resiratory syndrome coronavirus 2 (SARS-CoV-2) in 30 s. The ethanol-based formulation is also active against some non-enveloped test viruses in 60 s (suspension tests, EN 14476). In-vivo data on the formulations would provide a more reliable result on the virucidal efficacy on contaminated hands but are currently not available. Nevertheless, the most recent modifications should be adopted for use in healthcare.